(Male) infertility: what does it mean to men? : new evidence from quantitative and qualitative studies - Wischmann, Tewes; Thorn, Petra (Reproductive biomedicine online, 2013)
Scientific knowledge of the emotional repercussions of infertility on men remains limited and has only recently become the focus of social science research. Firstly, the current developments in research on the psychosocial impact of infertility on men through a search of the literature over the last 10 years are outlined in this paper. In the second section, issues raised in pretreatment counselling for men and their partner who consider donor insemination are described as this treatment typically raises many emotional issues. The results of more recent studies with sophisticated methodological design show that the emotional impact of infertility may be nearly balanced, suggesting that men do suffer as well and that they have to be addressed in infertility counselling too. The emotional and clinical aspects of donor insemination support the hypothesis that the emotional repercussions of infertility affect both sexes. In general, male factor infertility seems to be more stigmatized than other infertility diagnoses. Forthcoming studies have to differentiate between the psychological impact of infertility on women and men and their respective abilities to communicate easily about this distress. More studies on infertile men in non-Western societies need to be conducted in order to understand the cultural impact on infertility. According to an American study, almost half of the women but only 15% of the men consider infertility the most upsetting experience of their lives. It would be easy to assume that infertility is predominantly a female problem. However, this assumption is likely to be based on out-dated gender stereotypes and inadequate methodology. The results of much of the formerly available research supporting women’s greater overt distress in response to infertility may well reflect differences in the ways men and women have been socialized to cope with negative affect. More recent qualitative and quantitative research indicates that the emotional impact may be nearly balanced, suggesting that men do suffer as well and that they have to be addressed in infertility counselling too. In many cultures, male infertility remains a stigmatized condition and associated with a lack of virility and masculinity. For men, this may result in secrecy surrounding diagnosis, sometimes to the point where the female partner takes the blame for the couple’s inability to conceive. Based on qualitative and of recent quantitative research, this article will outline important aspects of (male) infertility and challenge the notion of the “emotionally unaffected” male. It will also draw on typical emotional and clinical aspects of donor insemination, a family-building alternative in which many emotional issues of male infertility culminate, thus supporting the hypothesis that the emotional repercussions of infertility affect both sexes similarly.
Gesehen am 18.11.2021